Capitalism's Deniers - Jonathan Nitzan; Shimshon Bichler (The Bichler and Nitzan Archives, 2019)
A new, capitalism-denying book is on the shelves, and it makes a stunning discovery: `Capitalism without competition is not capitalism'! Capitalist crisis, like climate change, tends to breed `capitalism deniers'. The problem, argue the deniers, lies not in capitalism but in its `distortions'. In its pure form, they maintain, capitalism is the best of all possible worlds. But to the deniers' chagrin, contemporary capitalism is no longer pristine. Unlike its original, once-upon-a-time version, its current one is subject to distorting `imperfections', `shocks' and `exogenous' events. And it is these aberrations – rather than capitalism itself – that should be blamed for the system's misfortunes.
Keywords: L; L1; P; 330; capitalism; competition; fundamentalism; ideology; neoclassical economics